2007
DOI: 10.1063/1.2827317
|View full text |Cite
|
Sign up to set email alerts
|

EPR Paradox, Locality and Completeness of Quantum Theory

Abstract: only with a specific protocol telling how the random experiment has to be performed. The probabilistic model used to prove BI implied a protocol completely inappropriate and impossible to implement for SPCE . Therefore we conclude that the important question whether QT is predictably complete is still open and we show how the unconventional analysis of the existing data could help to answer it. The correct understanding of statistical and contextual character of QT is essential for the research in the domain o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…16 Several authors pointed out that various proofs of Bell type inequalities use a counterfactual reasoning and suffer from a contextuality loophole . [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Therefore we do not doubt that Bell type inequalities can be and are violated in SPCE but the significance of the violation should be confirmed by additional homogeneity tests if it is possible. 15,16…”
Section: S Is a Simple Random Sample If And Only Ifmentioning
confidence: 99%
“…16 Several authors pointed out that various proofs of Bell type inequalities use a counterfactual reasoning and suffer from a contextuality loophole . [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Therefore we do not doubt that Bell type inequalities can be and are violated in SPCE but the significance of the violation should be confirmed by additional homogeneity tests if it is possible. 15,16…”
Section: S Is a Simple Random Sample If And Only Ifmentioning
confidence: 99%
“…Various probabilistic models used to prove inequalities are not consistent with experimental protocols used in SPCE [37,44]. If contextual character of quantum observables is properly taken into account correlations may be explained in intuitive way [28][29][30][31][32][33][40][41][42][43][44][45][46][47]. Moreover many experiments in quantum optics and in neutron interferometry can be simulated event by event in a local and causal way [51][52][53][54].…”
mentioning
confidence: 99%
“…As we explained in section 2 QM does not predict perfect correlation or anti-correlation of spin projections [29,[34][35][36][37][38][39][40]. Therefore if Bob and Alice decide before the experiment to choose the same experimental setting when Alice obtains a click on one of her detectors, in a particular time-window, she does not know with certainty whether Bob registers a click on his detector at the same time window.…”
Section: Entanglement and Instantaneous Influencesmentioning
confidence: 97%
“…If hidden variables depend on the settings then Bell-type inequalities may not be proven [29,[34][35][36][37][38][39][40]. Already in 1862, George Boole showed that whatever process generates a data set S of triples of variables (S 1 ,S 2 ,S 3 ) where S i = ±1, then the averages of products of pairs S i S j in a data set S have to satisfy the equalities very similar to Bell inequalities [52,55,56].…”
Section: Kolmogorov Models and Experimental Protocolsmentioning
confidence: 99%
See 1 more Smart Citation